Experiences of female companions of male prisoners inside and outside prisons - Brum, Rayssa Reck (2024)
This study aimed to understand the repercussions of prison for female companions of imprisoned men. Twelve female companions of male prisoners participated in the study. Data were collected through a sociodemographic data questionnaire and a semi-structured interview, and submitted to Thematic Analysis. There was an important change in the women’s entire lives after the arrest of their partners, considering experiences directly related to prison, as well as repercussions on their lives in general, which went beyond direct contact with the prison context. It is considered necessary to highlight the processes to which these women are exposed, as well as to legitimize their experiences, intertwined in a process of significant increase in incarceration in Brazil.